The Mary Wigman Book Her Writings (Wesleyan University Press, 1975)
The final testament of a great creative artist, whose genius as a dancer and choreographer was well matched by her verbal gifts. In this volume, Walter Sorell, her longtime friend, brings together a rich selection of her writings: warm letters, poems, anecdotes of her early years, witty cartoons, essays on the art of dance, and on some of her own works. Included are her reminiscences of her first compositions and performances, of the dancers who flocked to her company and school at Dresden, and of her triumphant American tours in 1930-1933. The Mary Wigman Book was originally published by Wesleyan in 1973.